Lightweight Design and Verification of Housings of Helicopter Reducers with Carbon Fiber Reinforced Composites - Yan Yuesheng; Wang Jichong; Cai Zhijie; Yin Hongling; Peng Xiongqi (Jixie chuandong)
The housing of a helicopter reducer system is lightweight designed by replacing cast aluminum alloy with carbon fiber reinforced composites. Under the condition of retaining the original design hard points and meeting the requirements of structural stiffness and strength, the lightweight design of the housing is achieved with a weight reduction of 21.8%. One quarter composite housing with 1∶1 scale is trial-manufactured with the hot pressure molding. Static and fatigue tests of the composite housing are carried out. The test results show that the composite housing is not damaged in the static test under 1.5 times the design load, and the number of fatigue test cycles under the design load reaches more than 20 000 times. This verifies the feasibility of light-weighting with the carbon fiber reinforced composite for the housing of the helicopter reducer system.